Repentance (tawbah) and its relationship with the human psyche from Qur'anic perspective - Adnin Najihah Zulkipli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study is designed to probe into the relationship between tawbah and human psyche. The Qur'ān in its numerous verses emphasized the effects of tawbah on human life. This includes tawbah as a measure to gain success, and; the absence of tawbah as a reason for man to become among the wrongdoers. The suggestive Quranic concept of tawbah indicates the presence of a strong relationship between tawbah and modification of human thinking and behaviour. However, few literatures highlighted the relationship between tawbah and human psyche. The purpose of this research is to examine the possible relationship between the two. This research employs qualitative method for data collection. Study of literatures helps to broaden the conceptual understanding underlying both terms throwing clear ideas specifically on the concept of tawbah and human psyche from Qur'anic perspective. An inductive and analytical approaches were adopted in order to analyse the relationship between tawbah and human psyche. The finding suggests that tawbah is very much related to the psyche as a curative measure (shifā') that heals the psyche from repercussion of sins such as self-fragmentation, emotional problems, and deterioration of character. Tawbah also gives man hope to change, to renew themselves, and to establish a more meaningful life through its constructive processes. The results of this study imply that knowledge about tawbah and its relationship with human psyche is crucial in helping man to develop one's behaviour simultaneously, designing a correct way of thinking and perceiving his existence in relation to his God and fellow human beings.